Moral Education in Early Childhood in the Era of the Covid-19 Pandemic - Indah Daratista; Muhammad Yusuf (Journal of Research in Islamic Education, 2021)
Education is a way to develop the potentials possessed by humans. Education that we have known since childhood is moral education. Moral education can be done since the child is in the womb, until he is an adult. But ideally, moral education is more effective when children are 4-5 years old. Moral education can be done by parents and educators at school, it can be done at home or at school. However, at this time, due to the Covid-19 virus, the government has temporarily suspended the face-to-face learning process with the aim of reducing the number of Covid-19 transmissions. Therefore, all levels of education, both higher education and early childhood education, are laid off, with an online learning system. Therefore, more responsibility in educating children's morals currently lies with parents who are at home. Because parents are always with their children, and understand their daily habits. Researchers want to examine whether parents of early childhood students guide their children's behavior well during the covid-19 pandemic, or do not care at all about children's learning and worship activities. The research method used is descriptive qualitative, with data reduction analysis techniques, data presentation and drawing conclusions. The results of the study concluded that parents are very important in moral education during the covid-19 pandemic. Parents should be more concerned with their children, and provide examples of good attitudes so that children can imitate them. By giving direct examples, advising, getting used to and giving punishment (positive punishment) to children, in introducing and telling about good morals. Because basically every parent wants their child to have good character.